The effectiveness of topical dimethicone together with a one health approach for the control of tungiasis in the Sanumás communities, Yanomami territory, Amazon rainforest: a real-world study - Santana, Yago Ranniere Teixeira (2023)
Background: The success of tungiasis treatment is highly dependent on adequate environmental control. Methods: This is a real-world observational cohort study designed to monitor the effectiveness of topical dimethicone together with a One Health approach for the control of tungiasis in the Sanumás communities, Amazon rainforest, Brazil. We followed up on 562 indigenous people and 81 domestic dogs for 1.5 years in a 3-month interval. A new molecular method for large-scale soil evaluation was also tested. The control of tungiasis was independently conducted by the Brazilian Ministry of Health and comprised topical dimethicone application (NYDA®) for humans, single-dose oral afoxolaner for dogs, and in-house soil fumigation with fipronil. The main outcome was the occurrence of tungiasis after the use of topical dimethicone together with the One Health approach. Results: A total of 49 of the 562 indigenous people had active tungiasis at enrollment (8.72%). Only three cases of tungiasis resulted in active lesions after the use of topical dimethicone together with the One Health approach, with two cases of recurrence. From the 6-month follow-up and after, soil infestation was not detected. Conclusions: We conclude that the use of NYDA® together with animal and environmental interventions are effective measures for the control of tungiasis.